1999
DOI: 10.2337/diacare.22.7.1105
|View full text |Cite
|
Sign up to set email alerts
|

Work disability and diabetes.

Abstract: Work disability is significantly higher for individuals with diabetes than for those without diabetes at all ages, and results in a significant decrease in earnings. A disproportionate burden of work disability is borne by older individuals and women with diabetes. Better information on the determinants of work disability in individuals with diabetes is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
1
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 0 publications
8
65
1
8
Order By: Relevance
“…For diabetes mellitus, we found only cross-sectional studies providing "determinants" of the relation between the disease and work disability. The determinants found were similar to the prognostic factors identified in the cohort studies in the present study, for example, age (high versus low) and gender (female versus male), both of which were positively associated with work disability, and education (high versus low) which was found to be negatively associated with work disability (73)(74)(75).…”
Section: Methodological Problemssupporting
confidence: 64%
“…For diabetes mellitus, we found only cross-sectional studies providing "determinants" of the relation between the disease and work disability. The determinants found were similar to the prognostic factors identified in the cohort studies in the present study, for example, age (high versus low) and gender (female versus male), both of which were positively associated with work disability, and education (high versus low) which was found to be negatively associated with work disability (73)(74)(75).…”
Section: Methodological Problemssupporting
confidence: 64%
“…It is known that people with limitations do work (5,6,16). It is also known that individuals determined to be disabled under the rules of the SSA for receipt of benefits under Social Security Disability Insurance fear loss of those benefits if they work; this disincentive keeps individuals on the disability rolls (13).…”
Section: Discussionmentioning
confidence: 99%
“…T h e association between diabetes and disability has not been well studied, but some researchers have found that disability is two to three times higher among people with diabetes than among those without diabetes (3)(4)(5)(6). Disability is a key indicator of the degree of morbidity associated with a chronic disease such as diabetes and a core component of the impact of chronic disease on quality of life.…”
mentioning
confidence: 99%